2021
DOI: 10.3390/polym13193327
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Demineralization Effects of Dental Adhesive-Composites on Enamel–Root Dentin Junction

Abstract: Oral biofilm reactor (OBR) and pH cycling (pHC) artificial caries model were employed to evaluate the anti-demineralization effects of four composite filling systems on enamel–root dentin junction. Sixty-four enamel–root dentin blocks (6 mm × 6 mm × 2 mm) each with a cylindrical cavity were randomly assigned to the pHC and OBR group, then four subgroups (n = 8) and filled with either the Beautifil II (BEF, SPRG-filler-containing) or Estelite (EST) composite after the adhesive (either Single Bond Universal (SBU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
0
8
0
1
Order By: Relevance
“…The typical in vitro demineralization–remineralization studies for simulating the cariogenic challenges in the mouth are classified into biofilm and chemical models [ 46 ]. Furthermore, chemical models are categorized into pH-cycling and simple mineralization models for artificial dental caries and dental erosion, respectively [ 47 ]. We conducted the simple mineralization model using an acid-eroded enamel surface to assay each repairing paste for a total duration of 30 min (i.e., each treatment of 10 min repeated three times).…”
Section: Resultsmentioning
confidence: 99%
“…The typical in vitro demineralization–remineralization studies for simulating the cariogenic challenges in the mouth are classified into biofilm and chemical models [ 46 ]. Furthermore, chemical models are categorized into pH-cycling and simple mineralization models for artificial dental caries and dental erosion, respectively [ 47 ]. We conducted the simple mineralization model using an acid-eroded enamel surface to assay each repairing paste for a total duration of 30 min (i.e., each treatment of 10 min repeated three times).…”
Section: Resultsmentioning
confidence: 99%
“…An important focus of research on new materials is to investigate their effect on the demineralisation of tissues at the tooth–restorative interface. The authors of [ 52 ] report that the use of the SPRG-filler-containing adhesive (i.e., FL Bond II) alone cannot effectively reduce the demineralisation of enamel, but if the SPRG-filler-containing composite is used in combination with it, then the cumulative synergy effect for anti-demineralisation becomes significantly higher. The restorations using a 10-MDP-containing adhesive (i.e., Single Bond Universal) with a composite resin filling appeared to reduce the demineralisation of the enamel, but it had no obvious effect when it was used on the root dentin.…”
Section: Discussionmentioning
confidence: 99%
“…Sample size calculation was based on a previous study with a similar study design that showed a statistically significant difference ( p < 0.050) between the ion-releasing materials and the control group [ 25 ]. A total of 56 teeth achieved 80% power and 0.05 type 1 error.…”
Section: Methodsmentioning
confidence: 99%